ECONOMIC FRAGMENTATION AND STRATEGIC RIVALRIES: IMPLICATIONS FOR NATIONAL SECURITY AND PROSPERITY IN NIGERIA - AKALE, CHARLES SOKOMBA; UDEGBUNAM, KINGSLEY CHIGOZIE (JOURNAL OF ECONOMICS AND ALLIED RESEARCH, 2025)
This paper investigates the intensifying phenomenon of economic fragmentation and its intricate linkage with strategic rivalries in the evolving global order, with particular emphasis on Nigeria's position and vulnerabilities. Against the backdrop of increasing geopolitical tensions, most notably the rivalry between major powers such as the United States and China. The research analyzes how emerging patterns of trade protectionism, technological decoupling, and the reconfiguration of global supply chains are reshaping the international economic landscape. These transformations are not only altering traditional economic alliances but are also heightening the risks faced by developing countries, particularly in terms of national security and sustainable economic development. By utilizing a mixed-methods approach that combines qualitative insights with quantitative data analysis, including the use of statistical tools, charts, and tables, the study offers a multidimensional understanding of the implications of global economic fragmentation. Key areas explored include trade disruptions, access to critical technologies, and the increasing reliance on regional economic blocs. The paper also interrogates the implications of these shifts for Nigeria’s strategic economic engagements within regional frameworks such as the Economic Community of West African States (ECOWAS) and the African Continental Free Trade Area (AfCFTA). The findings reveal that Nigeria is increasingly exposed to the cascading effects of global strategic rivalries, which manifest in reduced trade flexibility, technological dependencies, and heightened supply chain vulnerabilities. These developments pose substantial challenges to Nigeria’s national security architecture and long-term economic resilience. The paper concludes by recommending strategic policy realignments and regional cooperation mechanisms to mitigate the adverse effects of global economic fragmentation on Nigeria’s developmental trajectory